Proteinuria as an independent predictor of stroke: Systematic review and meta-analysis - Kelly, Dearbhla M (Int J Stroke, 2020)
BACKGROUND: Proteinuria has emerged as an important vascular risk factor for adverse cardiovascular events including stroke. Hypertension has been proposed as the principal confounder of this relationship but its role has not been systematically examined. AIM: We aimed to determine if proteinuria remains an independent predictor of stroke after more complete adjustment for blood pressure. SUMMARY OF REVIEW: We performed a systematic review, searching MEDLINE and EMBASE (to February 2018) for cohort studies or randomized controlled trials that reported stroke incidence in adults according to baseline proteinuria ± glomerular filtration rate. Study and participant characteristics and relative risks were extracted. Estimates were combined using a random effects model. Heterogeneity was assessed by χ(2) statistics and I(2), and by subgroup strata and meta-regression, with a particular focus on the impact of more complete adjustment for blood pressure on the association. The quality of cohort studies and post hoc analyses was assessed using the Newcastle–Ottawa Scale. We identified 38 studies comprising 1,735,390 participants with 26,405 stroke events. Overall, the presence of any level of proteinuria was associated with greater stroke risk (18 studies; pooled crude relative risk 2.00, 95%CI 1.63–2.46; p < 0.001) even after adjustment for established cardiovascular risk factors (33 studies; pooled adjusted relative risk 1.72, 1.51–1.95; p < 0.001), albeit with considerable heterogeneity between studies (p < 0.001; I(2 )= 77.3%). Moreover, the association did not substantially attenuate with more thorough adjustment for hypertension: single baseline blood pressure measure (10 studies; pooled adjusted relative risk = 1.92, 1.39–2.66; p < 0.001); history or treated hypertension (four studies; pooled adjusted relative risk = 1.76, 1.13–2.75, p = 0.013); multiple blood pressure measurements over months to years (four studies; relative risk = 1.68, 1.33–2.14; p < 0.001). CONCLUSIONS: Even after extensive adjustment for hypertension, proteinuria is strongly and independently associated with incident stroke risk, possibly indicating a shared renal and cerebral susceptibility to vascular injury that is not fully explained by traditional vascular risk factors.